Influence of dietary inclusion of xylanase from different sources on LingNan Chinese color-feathered chickens - XU, C L; ZUO, J J; FENG, D Y (The Indian Journal of Animal Sciences, 2011)
This study was conducted to research 2 single xylanase (XylnA, XylnD) (EC 3.2.1.8) cocktails. XylnA was from Aspergillus sp. and XylnD from Trichoderma reesei. Optimum temperature and pH of XylnA and XylnD was 45 Â°C and 4.5, respectively was 55 Â°C and 5.5 XylnA was inhibited by pepsin and trypsin. However XylnD was activated by pepsin and trypsin. XylnA was activated by Ca2+, Cu2+ and Zn2+. However XylnD was inhibited by Ca2+, Zn2+ and Fe2+. In vitro incubation of XylnA with XylnD at the ratio of 1:1 showed the highest synergistic effect of 1.84 on wheat cell wall degradation. The amounts of both reducing sugars and xyloses liberated from wheat cell walls were increased. 1800 one-day-old male LingNan Chinese color-feathered chickens were allotted to 5 treatments (a positive control diet (PC), a negative control diet (NC) with a lower energy density (approximately 0.66 MJ/kg feed) and 3 test diets where XylnA, XylnD and combination of XylnA and XylnD (1:1) were added to the negative control individually with the same enzyme activity (4000U/kg feed). Feed intake and body weight gain were significantly increased with XylnAD supplementation in comparison with NC and there was no difference in comparison with PC. However, growth performance was not significantly increased with single xylanase addition. It can be concluded that the combination of XylnA and XylnD supplementation to low-energy diet could improve growth performance over singe xylanase.